Answer:
D. y <-x - 3
Explanation:
-3x + 2y > 5y + 9
Subtract 2y from 5y on the other side
5y - 2y = 3y
-3x > 3y + 9
Add 3x and put it the other side
0 > 3x + 3y + 9
Subtract 3y and put it on the other side
0 - 3y = -3y
-3y > 3x + 9
Divide by -3 on both sides
-3y/-3 > 3x + 9/-3
-3y/-3 = y
3x + 9/-3 = -x - 3
y > -x - 3
MOST IMPORTANT STEP OF ALL: Switch the inequality sign around because you divided with a negative number which is -3. That's a rule in inequality.
y < -x - 3
So your final answer is y < -x - 3